Impacts of sea level rise on economic growth in developing Asia - Ruben Carlo Asuncion; Minsoo Lee (Asian Development Bank (ADB), 2017)
Global sea level rise (SLR) variations have undeniably begun to make an impact on highly vulnerable economies. These impacts of SLR are a key component of the projected economic damage of climate change, an important input to climate change policies and adaptive measures. This paper considers SLR projections and its impact on the economy and includes a consolidation of various related studies. Estimated global gross domestic product (GDP) loss by 2100 ranges from 0.3% to as high as of 9.3% (Hinkel et al. 2014; Pycroft, Abrell, and Ciscar 2015). Climate change impact should be addressed at the global level through a locally focused effort where education and acceptance by all stakeholders are crucial and warranted. Further, this paper tackles several adaptive strategies as a response to SLR which include retreat, accommodation, and protection. The retreat strategy simulates that SLR causes the loss of inundated land and incurs planned relocation (migration) costs above a certain sea level. The accommodation strategy allows usage of vulnerable areas or land and limits damage by floodproofing or raising structures. Finally, the protection strategy projects that land will be protected from SLR damage by sea walls or other barriers of a certain height. On the other hand, Diaz (2016) estimates a median adaptation cost from migration at 16% of GDP under the least-cost strategy by 2050. In general, the education of and the acceptance by the concerned local community will be crucial in the successful implementation of SLR adaptation strategies, notwithstanding parallel mitigation efforts on a global scale.
Keywords: Q50; Q54; 330; climate change; economic growth; sea level rise